Limitations to recovery following wildfire in dry forests of southern Colorado and northern New Mexico, USA. Issue 1 (1st October 2019) - Rodman, Kyle C.; Veblen, Thomas T.; Chapman, Teresa B.; Rother, Monica T.; Wion, Andreas P.; Redmond, Miranda D.
Abstract: Climate warming is contributing to increases in wildfire activity throughout the western United States, leading to potentially long‐lasting shifts in vegetation. The response of forest ecosystems to wildfire is thus a crucial indicator of future vegetation trajectories, and these responses are contingent upon factors such as seed availability, interannual climate variability, average climate, and other components of the physical environment. To better understand variation in resilience to wildfire across vulnerable dry forests, we surveyed conifer seedling densities in 15 recent (1988–2010) wildfires and characterized temporal variation in seed cone production and seedling establishment. We then predicted postfire seedling densities at a 30‐m resolution within each fire perimeter using downscaled climate data, monthly water balance models, and maps of surviving forest cover. Widespread ponderosa pine ( Pinus ponderosa ) seed cone production occurred at least twice following each fire surveyed, and pulses of conifer seedling establishment coincided with years of above‐average moisture availability. Ponderosa pine and Douglas‐fir ( Pseudotsuga menziesii ) seedling densities were higher on more mesic sites and adjacent to surviving trees, though there were also important interspecific differences, likely attributable to drought and shade tolerance. We estimated that postfire seedling densities in 42% (for ponderosa pine) and 69% (for Douglas‐fir) of the total burned area were below the lowest reported historical tree densities in these forests. Spatial models demonstrated that an absence of mature conifers (particularly in the interior of large, high‐severity patches) limited seedling densities in many areas, but 30‐yr average actual evapotranspiration and climatic water deficit limited densities on marginal sites. A better understanding of the limitations to postfire forest recovery will refine models of vegetation dynamics and will help to improve strategies of adaptation to a warming climate and shifting fire activity.